Odpowiedzi

2010-03-06T14:42:06+01:00
E) 4x-4=3x+3
4x-3x=3+7
x=10

g) x= 1-3x-3
4x=-2 /:4
x=-½
2010-03-06T14:44:48+01:00
3*(2x-2)=x
6x-6=x
5x=6
x=6/5

3*(2x+3)=x-1
6x+9=x-1
5x=-10
x=-2

4*(x-1)=3*(x+1)
4x-4=3x+3
x=7

-(x-1)=2
-x+1=2
-x=1
x=-1

x=1-3(x+1)
x=1-3x-3
4x=-2
x=-1/2

(x+1)-(x-1)=1
x+1-x+1=1
0=-1 sprzeczne
1 5 1
2010-03-06T15:03:13+01:00
C) 3*(2x-2)=x
6x-6=x
6x-x=6
5x=6 /:5
x=1.2

d)3*(2x+3)=x-1
6x+9=x-1
6x-x=-1-9
5x=-10 /:5
x=-2

e)4*(x-1)=3*(x+1)
4x-4=3x+4
4x-3x=4+4
x=8

f)-(x-1)=2
-x+1=2
1-2=x
-1=x

g) x=1-3(x+1)
x=1-3x-3
x+3x=1-3
4x=-2/:4
x=-0,5

h)(x+1) - (x-1)=1
0=1

Mam nadzieję że dobrze są rozwiązane ;-)
Pozdrawiam.